2019
DOI: 10.1186/s12913-019-4505-3
|View full text |Cite
|
Sign up to set email alerts
|

Policy analysis of the Iranian Health Transformation Plan in primary healthcare

Abstract: Background Health systems reform is inevitable due to the never-ending changing nature of societal health needs and policy dynamism. Today, the Health Transformation Plan (HTP) remains the major tool to facilitate the achievements of universal health coverage (UHC) in Iran. It was initially implemented in hospital-based setting and later expanded to primary health care (PHC). This study aimed to analyze the HTP at the PHC level in Iran. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 44 publications
1
54
0
1
Order By: Relevance
“…Some advocated for revisiting how healthcare sectors are being financed and suggested forgoing private health insurance as the least sustainable and equitable methods of healthcare financing. Others stressed that besides primary health care (PHC) and UHC, social health insurance (SHI) should be given priority in all and not just low- and middle-income countries (LMICs) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some advocated for revisiting how healthcare sectors are being financed and suggested forgoing private health insurance as the least sustainable and equitable methods of healthcare financing. Others stressed that besides primary health care (PHC) and UHC, social health insurance (SHI) should be given priority in all and not just low- and middle-income countries (LMICs) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary health care is delivered via a network of district health clinics, which is an independent authority from the MoHME, provided by hospitals and coordinated/regulated by treatment deputy of medical universities under the supervision of MoHME. Tertiary health services are provided predominantly in big cities by private and public hospitals and coordinated/regulated by MoHME [ 3 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, different organizations and stakeholders should make appropriate policies in this respect. Studies show that, similar to other countries [12], there are conflicts of interest among stakeholders in the healthcare system and that health priorities are not prioritized properly in Iran [13]. Adhikari et al evaluated the Malawian health system stakeholders and showed that having problems in coordinating between stakeholders would create many problems for health system policies [14].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, the Iranian health system has implemented several policy plans such as Primary Health Care(PHC) network (1985) [10], National Health Insurance coverage program [11], and rural family physician program(2004) [12] to improve health status and achieve to UHC. These resulted in the improvement of some health outcomes like life expectancy at birth, and mother and child morbidity and mortality rates [12,13]. Along with other challenges to implementing and continuing the policy reforms, the financing dimension of the reforms has also been a pivotal and challenging issue…”
Section: Introductionmentioning
confidence: 99%